2007
DOI: 10.1007/s10911-007-9041-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Progression: Controversies and Consensus in the Molecular Mechanisms of Metastasis and EMT

Abstract: Breast cancer is the second most frequent form of female cancer and a major source of cancer death worldwide. Although breast cancer has long been part of the human condition, appearing in the writings of ancient Egyptians, modern breast cancer shows a disturbing statistical increase from 1 per 20 women in the 1960s to one in eight today [1]. Although early detection by mammography and adjuvant therapies has improved survival, the absence of good prognostic criteria continues to result in overtreatment of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
2
25
0
4
Order By: Relevance
“…6 In cancer research, the term EMT has been more inclusively referred to as a change of cytological phenotype characterized as loss of cell junction and gain of migratory behaviors. 40,45 In the present study, we demonstrated that deposition of TNC is frequently observed in invasion fronts of cancer cells with a scattered morphology, and that TNC induces EMT-like morphological change of MCF-7 cells, featuring loss of intercellular connections and an increasingly locomotive phenotype. The similar morphological change of MCF-7 cells on TNC substratum previously has been reported, but it was not mentioned as EMT.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…6 In cancer research, the term EMT has been more inclusively referred to as a change of cytological phenotype characterized as loss of cell junction and gain of migratory behaviors. 40,45 In the present study, we demonstrated that deposition of TNC is frequently observed in invasion fronts of cancer cells with a scattered morphology, and that TNC induces EMT-like morphological change of MCF-7 cells, featuring loss of intercellular connections and an increasingly locomotive phenotype. The similar morphological change of MCF-7 cells on TNC substratum previously has been reported, but it was not mentioned as EMT.…”
Section: Discussionsupporting
confidence: 57%
“…38 However, whether classic EMT, including an ordered series of transcriptional events and a switch in cell fate observed in embryogenesis, occurs during tumor invasion and metas- tasis is still controversial. 39,40 In ductal carcinomas of the breast, immunohistochemical studies have not demonstrated any apparent correlation of E-cadherin expression with the scattered morphology, tumor type, nodal status, disease recurrence, distant metastases, or other prognostic factors. [41][42][43][44] These observations suggest that a complete transition to a mesenchymal phenotype associated with transcriptional switching is not required for increased malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that metastatic progression may involve transient EMT that facilitates the migratory behavior of cancer cells (Cowin and Welch, 2007). In this regard, it is interesting to note that elevated expression of ILK in either established mammary epithelial cell or primary mammary epithelial cells is associated with an EMT phenotype (Somasiri et al, 2001;White et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…EMT is often activated in tumors during invasion and metastasis and helps cancer cells detach from solid tumors. EMT is characterized by loss of intracellular adhesion (loss of E-cadherin); loss of epithelial markers such as cytokeratins 8/18 and upregulation of mesenchymal markers such as vimentin and acquisition of fibroblastlike spindle morphology and increased motility (3,4). Previously, we showed that treatment of triple-negative cells of basal origin that have a mesenchymal phenotype with HDAC inhibitor entinostat results in reversal of EMT phenotype and reduction in migratory capacity (5).…”
Section: Introductionmentioning
confidence: 99%